ANALISIS PENILAIAN PRESTASI PEGAWAI (PERFORMANCE APPRAISAL) DAN PENGARUHNYA TERHADAP KOMPENSASI PEGAWAI SERTA TERHADAP KEPUASAN KERJA - Samsul Hadi (Akutansi Bisnis & Manajemen ( ABM ), 2000)
This research has as its rationale that if employees of the company are satisfied, they would work better, be more productive, and have a good attitude. Therefore management should consider an effort to achieve employee satisfaction in order they work well. Job satisfaction can be influenced by many kind of compensations, both of direct and indirect compensations. Job satisfaction of the employees can cause of perception that employees performance is appreciated objectively and fairly, which is how they appreciated in the performance appraissal. Each individual has their own concentration of need achievement. Therefore, managers should decide and predict the compensation that satisfy their employees to enhance the work performance. This research aimed to determine which kind of compensations influence the job satisfaction. The fair compensation depends on internal, external, and social factors. One of these factors is based on the conducting of performance appraissal include : methods, aspects, and deciding the staffs who conduct the appraissal. The results of better management, and fair performance appraissal can be used for deciding the payment and salary of the employees. Fair compensation may create job satisfaction and afterward enhance the productivity and performance of the employees. In other words, perception that if they treat fairly, they would be satisfied. Finally they enhance their productivity and work performance. This research conducted at PT. Gatra Mapan Malang in 1999. The purpose of this research is to study the influence of performance appraissal on the job satisfaction of the employees. Eighty five samples were taken using ?Proportional Random Sampling? methods through the population of 561 employees from every department. Data were analyzed by using regression and path analysis. The results of this study showed that most of employees agree and very agree for : - Using rating scale methods - Considering reliability, ability, creativity, discipline, attitude, cooperativity, and leadership factor in performance appraissal. - Supervisory appraise is direct supervisor - The result of performance appraissal used for determining direct compensation Inferential statistic showed significant relation are : 1. appraissal methods, appraissal factors, supervisory appraise toward performance score, together or partially. 2. performance score toward direct compensation and job satisfaction. And non significant relation are : 1. performance score toward indirect compensation 2. indirect compensation toward job satisfaction.